2014
DOI: 10.1186/2047-1440-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Organ and tissue donation in clinical settings: a systematic review of the impact of interventions aimed at health professionals

Abstract: In countries where presumed consent for organ donation does not apply, health professionals (HP) are key players for identifying donors and obtaining their consent. This systematic review was designed to verify the efficacy of interventions aimed at HPs to promote organ and tissue donation in clinical settings. CINAHL (1982 to 2012), COCHRANE LIBRARY, EMBASE (1974 to 2012), MEDLINE (1966 to 2012), PsycINFO (1960 to 2012), and ProQuest Dissertations and Theses were searched for papers published in French or Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
0
17
0
4
Order By: Relevance
“…HCPs’ involvement in this process cannot be overemphasised as they are considered to be the primary intermediaries between organ donors and transplant recipients (Abidin et al., ; De Groot et al., ). The success, therefore, or otherwise of the ODT process, rests (albeit not exclusively) with HCPs (Douville et al., ). It also pivots on a number of other factors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…HCPs’ involvement in this process cannot be overemphasised as they are considered to be the primary intermediaries between organ donors and transplant recipients (Abidin et al., ; De Groot et al., ). The success, therefore, or otherwise of the ODT process, rests (albeit not exclusively) with HCPs (Douville et al., ). It also pivots on a number of other factors.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the benefits, there remains a global shortage of organs for transplantation. Because this shortage does not hinge on the absence of suitable organs, the disequilibrium between ODT has been blamed, globally, on HCPs (Douville et al., ). It is, however, maintained in this review that rather than blame HCPs for this disequilibrium, it is a combination of HCPs’ attitudes and experiences as well as time constraints, conflict of interests, the altruistic nature of ODT and organ donation rules, which account for this global disequilibrium (Douville et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although they lacked robust methodologies, 5 studies demonstrated that interventions have a significant effect on HCP behaviors, namely in terms of referring potential donors, approaching donors' families, and securing a donated organ. 22 Another study by McGlade and associates demonstrated that a 33-hour integrated course on organ procurement and clinical care of potential organ donors improved nursing students' knowledge of organ suitability after death, their ability to obtain consent, and their understanding of organ donation legislation and the definition of death. 23 Accordingly, there is a need to consolidate organ transplant teachings into health care education and to educate HCPs about the intricate nuances of donor identification, approaching the family, and respecting the ethical and legal considerations of donation.…”
Section: Introductionmentioning
confidence: 99%